Analisis Dampak Korupsi Pada Masyarakat (Studi Kasus Korupsi Pembangunan Shelter Tsunami di Kecamatan Labuan Kabupaten Pandeglang) - Susi Amalia (Epistemik: Indonesian Journal of Social and Political Science, 2022)
This study describes impact analysis of corruption cases on society (case study of tsunami shelter development in Labuan District, Pandeglang Regency. The corruption case in the construction of this shelter was carried out by the Ministry of Public Works and Publik Housing (KemenPUPR) and PT. Tidar Sejahtera with a project value of 18 billion rupiahs sourced from the State Revenue and Expenditure Budget (APBN), and caused state losses of 16 Billion rupiahs. This Study discusses the analysis of the impact on society of corruption casws caused by corruption caseof tsunami shelter construcyion in Labuan District, Pandeglang Regency using the theory of the impact of economic corruption from Mauo (1998) and I Ketut (2018), as well as the impact of social corruption and enforcement sfrom Wilhelmus (2017). The research method use is descriptive qualitative research. The results of this study were corruption in the construction of tsunami shelters carried out by KemenPUPR and PT.Tidar Sejahtera which had several impacts on the economic, social and law enforcement sectors. Where because of the corruption case, the buildings that were built were of low quality, there was no treatment from the local government, and the sentence impose on the defendant was not in accordance with the lawbecause the defendant was cooperative at the time of trial and still had family dependents.